Human metabolic responses to microgravity simulated in a 45-day 6° head-down tilt bed rest (HDBR) experiment. Issue 22 (28th April 2016) - Chen, Pu; Yu, Yanbo; Tan, Chen; Liu, Hongju; Wu, Feng; Li, Hongyi; Huang, Jianying; Dong, Haisheng; Wan, Yumin; Chen, Xiaoping; Chen, Bin
Abstract : Metabolomics approaches could achieve accurate and comprehensive analysis in human space exploration. Abstract : Sustainable human space exploration could progress further with the development of strategies and preparatory activities. However, this progression is largely dependent on ground-based experimental programmes that reflect the limitations of space. The head-down bed rest (HDBR) model simulates the effects of weightlessness on humans. While many physiological indices and their associations with HDBR-induced weightlessness have been well documented in the last several years, the underlying molecular mechanisms remain unknown. Therefore, we used a 6° HDBR model, combined with a metabolomics approach, to reveal novel molecular mechanisms underlying the human responses to weightlessness. A total of 7 volunteers (male, 26.13 ± 4.05 years) were recruited for a standard 45-day HDBR experiment, and their physiological indices associated with bone, muscle, and the gut microbiota were measured. Furthermore, urine samples were collected in nine different phases and analysed using one-dimensional proton nuclear magnetic resonance spectroscopy ( 1 H-NMR) to investigate human metabolic responses to HDBR. The results showed that the urinary excretion of metabolites associated with the deconditioning of bone, muscle and the gut microbiota in response to HDBR changed dramatically over the 45-day experimental period. Meanwhile, the bone, muscle and gut microbiota of the subjects declined after HDBR. Thus, bioinformatics approaches, such as metabolomics analysis, could achieve a more accurate and comprehensive analysis and subsequently provide new insight.